2003
DOI: 10.4141/a02-001
|View full text |Cite
|
Sign up to set email alerts
|

Savaging behaviour in domestic gilts: A study of seven commercial farms

Abstract: Harris, M. J. and Gonyou, H. W. 2003. Savaging behaviour in domestic gilts: A case study of seven commercial farms. Can. J. Anim. Sci. 83: 435-444. Piglet-directed aggression at farrowing was investigated on seven large, new pig units. Gilts were subject to a light (continuous or diurnal light) and/or sound (newborn piglet vocalisations or no vocalisations) treatment around the time of farrowing. Behaviour records were collected for the first farrowing of 6625 crossbred gilts. The incidence of savaging, number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…Most studies related to "savaging" are restricted to gilts (Marchant Forde 2002;Ahlström et al 2002), as piglet directed aggression is believed to be more frequent in young animals than in sows. In a previous study involving the first farrowing cycle, that is the initial period of approximately 5 mo when all breeding animals were gilts, on several new commercial farms, we reported that 2.9% of gilts killed one or more of their piglets (Harris and Gonyou 2003). A similar large-scale study is needed to assess the relative frequency of savaging by gilts and sows.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies related to "savaging" are restricted to gilts (Marchant Forde 2002;Ahlström et al 2002), as piglet directed aggression is believed to be more frequent in young animals than in sows. In a previous study involving the first farrowing cycle, that is the initial period of approximately 5 mo when all breeding animals were gilts, on several new commercial farms, we reported that 2.9% of gilts killed one or more of their piglets (Harris and Gonyou 2003). A similar large-scale study is needed to assess the relative frequency of savaging by gilts and sows.…”
mentioning
confidence: 99%
“…The third hypothesis was that sows that savaged during their first farrowing would be more likely to savage during their second parity than would those that did not savage as gilts (Lewis and Oakley 1970;Spicer et al 1985). The final hypothesis was that savaging incidence would be reduced by auditory and illumination modifications (Harris and Gonyou 2003).…”
mentioning
confidence: 99%
See 3 more Smart Citations